PERBANDINGAN KUALITAS CITRA HARD COPY DENGAN HASIL DIGITIZER DAN KAMERA SAKU PADA FOTO POLOS DADA KASUS TUBERKULOSIS DI BAGIAN RADIOLOGI RSUP DR. SARDJITO - , GALUH KARTIKA DEWI, Dr. dr. Lina Choridah, Sp.Rad(K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : One of supporting examination on tuberculosis is chest X-ray and Indonesia need teleradiology to resolve our problem about geographic conditions and too few radiologists. But teleradiology has to be supported by good imaging quality. Objective : To know about image quality differences and diagnostic suitability between hard copy and soft copy digitized by digitizer and pocket camera on chest X-ray for diagnosing tuberculosis Method dan Material : Observational study on 30 Chest X-ray with tuberculosis sign. Data from work station is printed to hard copy, and digitized by digitizer and pocket camera. Compare the image quality of hard copy and soft copy digitized by digitizer and pocket camera. Results :Comparison of image quality between hard copy and digitizer is p=1.000, Comparison of image quality between hard copy and pocket camera is p=0.000, Comparison of diagnostic suitability between hard copy and digitizer is p=1.000, and Comparison of diagnostic suitability between hard copy and pocket camera is p=1.000. Conclusion :There is no significant difference in image quality between hard copy and soft copy by digitizer (p>0.05), although hard copy has a better image quality than soft copy by pocket camera (p<0.05). There is no significant difference in diagnostic suitability between hard copy and soft copy by digitizer and pocket camera (p>0.05).